2007
DOI: 10.1158/1078-0432.ccr-06-1987
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4-Mediated Breast Cancer Metastasis: A Potential Role for Heparinoids?

Abstract: Purpose: The pattern of breast cancer metastasis may be determined by interactions between CXCR4 on breast cancer cells and CXCL12 within normal tissues. Glycosaminoglycans bind chemokines for presentation to responsive cells. This study was designed to test the hypothesis that soluble heparinoid glycosaminoglycan molecules can disrupt the normal response to CXCL12, thereby reducing the metastasis of CXCR4-expressing cancer cells. Experimental Design: Inhibition of the response of CXCR4-expressing Chinese hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 41 publications
5
64
0
2
Order By: Relevance
“…Our results are also consistent with results using 125 I-CXCL8 and 125 I-CCL3 with CXCR1-, CXCR2-, or CCR1-transfected CHO cell membranes [36], as well as with data from various laboratories showing that soluble heparin and heparan sulfate inhibit leukocyte responses [40,42]. Unfractionated heparin and the low MW heparin Tinzaparin inhibit CXCL12 binding to CXCR4-expressing CHO cells and human breast cancer cell lines, thus blocking signaling; these compounds might be useful in preventing chemokinedriven breast cancer metastasis [43].…”
Section: Effect Of Gag On Cxcl12 Binding To Cxcr4supporting
confidence: 88%
“…Our results are also consistent with results using 125 I-CXCL8 and 125 I-CCL3 with CXCR1-, CXCR2-, or CCR1-transfected CHO cell membranes [36], as well as with data from various laboratories showing that soluble heparin and heparan sulfate inhibit leukocyte responses [40,42]. Unfractionated heparin and the low MW heparin Tinzaparin inhibit CXCL12 binding to CXCR4-expressing CHO cells and human breast cancer cell lines, thus blocking signaling; these compounds might be useful in preventing chemokinedriven breast cancer metastasis [43].…”
Section: Effect Of Gag On Cxcl12 Binding To Cxcr4supporting
confidence: 88%
“…Overexpression of chemokine receptors or ligands can lead to enhanced survival, migration, and unchecked growth of the tumor cells (6). Some current therapies are designed to block the up-regulated chemokine receptors as a treatment for cancer and cancer metastasis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that CXCL12 promotes the growth and tumorigenicity of GBC through interaction with CXCR4. CXCL12 is involved in cell migration, invasion, and adhesiveness in several types of cancer (13,22,23,27). In this study, GBC cells showed enhanced motility and invasiveness in response to CXCL12.…”
Section: Discussionmentioning
confidence: 62%
“…It has been shown that CXCL12 is closely involved in motility, invasiveness, adhesiveness, and survival of several types of tumors (13,22,27). To address this issue, we also examined the effect of CXCL12 on motility and invasiveness of GBC cells using Transwell filter assays.…”
Section: Cxcl12 Increases Migration Invasion Adhesiveness and Survmentioning
confidence: 99%
See 1 more Smart Citation